Management of Regmatogent Retinal Ablation by Buckle Sclera and Cryoteraphy - Faneisha; AK Ansyori; Ramzi Amin (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2020)
Introduction: The most common type is regmatogen retinal detachment (rhegmatogenous retinal detachment), which is a result of the process of tearing of the retinal layer. The principle of operative management of retinal detachment is to reattach the detached layer of the retina by previously identifying and closing if there is a retinal tear and releasing traction from vitreoretina. Actions can include sclera buckle, pars plana vitrectomy and pneumatic retinopexy. The consideration of the choice of operative therapy is dependent on the pathogenesis underlying each case of retinal detachment. Case presentation: This case report found complaints of patients with sudden blurred vision without red eyes or calm eye conditions and a diagnosis with regmatogen retinal detachment. From the history, in this patient was obtained, complaints of blurred vision such as closed curtains complained of the patient and complaints were preceded by views such as seeing flashes of light or photopsia and vision such as flying objects or floaters which are the most common complaints in 50% of patients with retinal regmatogen retention. occurs because of the lattice degeneration process. In cases of severe and extensive retinal detachment, the combination procedure for vitrectomy and scleral buckle is the primary choice for optimal outcome. Conclusion: At follow-up, posterior segment examination revealed retinal attachments that were uncomplicated. Follow up 2 weeks post therapy found that the retina was attached and had vision with improvement.